Pattern of Follicular Development, CL Size, Steroid Hormones and Biochemical Profile during Early Pregnancy in Heifers and Cows - Hadiya, KK; Dhami, AJ; Lunagariya, PM; Sarvaiya, NP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The follicular development, CL size, plasma progesterone (P4), estradiol-17β (E2), total cholesterol and blood glucose profiles were  studied in 6 post-pubertal cyclic heifers and 6 postpartum cyclic cows each of Gir and HF x Kankrej breeds at weekly interval from  day 0 (estrus/AI) to day 21 post-AI and then on days 23, 28, 35 and 42 in non-return cases. The mean CL size in heifers (irrespective of  breeds) as monitored by transrectal ultrasonography on days 0, 7, 14, 21, 23, 28, 35 and 42 post-AI was found to be 4.72 ± 0.33, 12.30  ± 0.55, 12.72 ± 0.62, 8.74 ± 1.39, 9.47 ± 1.17, 11.83 ± 0.87, 14.44 ± 0.61 and 14.50 ± 0.67 mm, respectively. Plasma P4 concentrations on  corresponding days were 0.49 ± 0.10, 3.16 ± 0.21, 5.18 ± 0.41, 3.01 ± 0.99, 3.50 ± 0.96, 5.66 ± 0.73, 8.54 ± 0.21 and 8.96 ± 0.15 ng/ml,  respectively. The mean follicular size in heifers on days 0, 7, 14, 21, 23, 28, 35 and 42 post-AI was 12.70 ± 0.51, 5.86 ± 0.52, 5.23 ± 0.45,  9.21 ± 0.96, 7.41 ± 0.91, 6.14 ± 0.48, 4.80 ± 0.51 and 4.94 ± 0.30 mm, respectively. Plasma E2 concentrations on corresponding days were  56.08 ± 2.98, 29.58 ± 2.52, 20.25 ± 2.43, 38.08 ± 5.70, 22.66 ± 4.97, 21.58 ± 2.84, 15.80 ± 2.53 and 22.40 ± 3.29 pg/mL, respectively. Nearly  similar values and trend of observations were recorded for CL/follicular size and plasma P4/E2 profile in postpartum cows. The values of  CL size and plasma P4 were the lowest, and those of follicle size and plasma E2 were the highest on the day of estrus/AI, changed highly  significantly (p
Keywords: CL Size; Crossbred; Gir; Follicular Dynamics; Normal cyclic cattle; Steroid Hormones; Biochemical Profile